2010
DOI: 10.1016/j.quascirev.2010.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The sedimentary legacy of a palaeo-ice stream on the shelf of the southern Bellingshausen Sea: Clues to West Antarctic glacial history during the Late Quaternary

Abstract: a b s t r a c tA major trough ("Belgica Trough") eroded by a palaeo-ice stream crosses the continental shelf of the southern Bellingshausen Sea (West Antarctica) and is associated with a trough mouth fan ("Belgica TMF") on the adjacent continental slope. Previous marine geophysical and geological studies investigated the bathymetry and geomorphology of Belgica Trough and Belgica TMF, erosional and depositional processes associated with bedform formation, and the temporal and spatial changes in clay mineral pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 122 publications
(245 reference statements)
2
32
0
Order By: Relevance
“…From this, three main facies have been identified which are described and interpreted below and illustrated in Figure 2 and supplementary Figure S1. The facies succession broadly follows that documented for sediments recovered in the western ASE Hillenbrand et al, 2010b) and elsewhere on the Antarctic continental shelf (Domack et al, 1999Licht et al, 1999;Evans et al, 2005;Anderson, 2005, 2007;Ó Cofaigh et al, 2005;Hillenbrand et al, 2005Hillenbrand et al, , 2010aHillenbrand et al, ,b, 2013Pudsey et al, 2006;Heroy et al, 2008;McKay et al, 2008) with a muddy diamicton at the base of the sequence, overlain by a transitional muddy sand/sandy-gravel which in turn is capped by a terrigenous to biogenic mud. The primary purpose of our facies approach is to establish the major depositional environments (subglacial, glacier proximal and open marine) to inform and direct our dating strategy.…”
Section: Lithological Units and Facies Schemesupporting
confidence: 60%
See 2 more Smart Citations
“…From this, three main facies have been identified which are described and interpreted below and illustrated in Figure 2 and supplementary Figure S1. The facies succession broadly follows that documented for sediments recovered in the western ASE Hillenbrand et al, 2010b) and elsewhere on the Antarctic continental shelf (Domack et al, 1999Licht et al, 1999;Evans et al, 2005;Anderson, 2005, 2007;Ó Cofaigh et al, 2005;Hillenbrand et al, 2005Hillenbrand et al, , 2010aHillenbrand et al, ,b, 2013Pudsey et al, 2006;Heroy et al, 2008;McKay et al, 2008) with a muddy diamicton at the base of the sequence, overlain by a transitional muddy sand/sandy-gravel which in turn is capped by a terrigenous to biogenic mud. The primary purpose of our facies approach is to establish the major depositional environments (subglacial, glacier proximal and open marine) to inform and direct our dating strategy.…”
Section: Lithological Units and Facies Schemesupporting
confidence: 60%
“…In this context, the scarcity of calcareous (micro-)fossils in combination with the large and variable input of reworked fossil organic carbon from the hinterland has hampered efforts to establish a detailed retreat histories, especially when attempting to constrain the subglacial to glacier-proximal transition. Notwithstanding these problems, recent studies from the Bellingshausen Sea and western ASE shelf have demonstrated that with a careful sampling strategy guided by detailed sedimentological information, reliable deglacial chronologies can be produced using the acid insoluble organic (AIO) fraction (Hillenbrand et al 2010a;Smith et al, 2011). This approach requires a local reservoir correction, achieved by dating the surface sediments (usually obtained from box cores) and subtracting this age from down-core ages (cf.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most easily accomplished in modern temperate, meltwater-dominated glacial systems, because sediment production is elevated and thus signal generation is the strongest, resulting in higher mass fluxes that produce the accumulation rates necessary to resolve the recent or short-timescale ice response function Dowdeswell et al, 1998;Dowdeswell and Siegert, 1999;Jaeger and Nittrouer, 1999a;Jaeger, 2002;Andresen et al, 2012;. For modern iceberg-dominated systems, reduced production and flux of sediment to the sink limits our ability to quantify the relationship between ice flux (velocity) and the stratigraphic signal for short (sub-annual to decadal) timescales (Harden et al, 1992;Domack and McClennen, 1996;Lowe and Anderson, 2002;Hillenbrand et al, 2010a;Kirshner et al, 2012;Boldt et al, 2013). Consequently, the greatest advances in linking ice dynamics at modern to Quaternary advance-retreat time scales to sedimentary signal preservation exist for meltwater-dominated systems (Fig.…”
Section: The Sink-fidelity Of the Glacigenic Signalmentioning
confidence: 99%
“…Ice extent and dynamics in the Antarctic marine realm are determined from dating subglacial to glacimarine to open-marine lithofacies transitions (see Anderson et al, 2014;Cofaigh et al, 2014;Hillenbrand et al, 2014;Hodgson et al, 2014;Larter et al, 2014;Mackintosh et al, 2014 for cited studies). Because of the scarcity of calcareous fossils in Antarctic shelf sediments, it is particularly challenging to use marine 14 C to develop constraints on the timing of deglaciation and the accompanying sediment flux Andrews et al, 1999;Hall, 2009;Hillenbrand et al, 2010a;Larter et al, 2014;Licht and Andrews, 2002). In light of these dating challenges, the ability to recognize the large-scale regional controls on ice extent (e.g., shelf bathymetry, oceanographic forcing) is easiest when all chronological controls are synoptically summarized Cofaigh et al, 2014;Hillenbrand et al, 2014;Larter et al, 2014).…”
Section: Post-lgm Deglacial Timescalesmentioning
confidence: 99%